Decoupling Between Phytoplankton Growth and Microzooplankton Grazing Enhances Productivity in Subantarctic Waters on Campbell Plateau, Southeast of New Zealand. Issue 2 (20th February 2020) - Gutiérrez‐Rodríguez, A.; Safi, K.; Fernández, D.; Forcén‐Vázquez, A.; Gourvil, P.; Hoffmann, L.; Pinkerton, M.; Sutton, P.; Nodder, S. D.
Abstract: The Subantarctic zone is one of the largest High‐Nutrient Low‐Chlorophyll zones of the Southern Ocean. Despite widespread iron limitation, phytoplankton accumulation (chlorophyll a (chl a ) > 0.3 mg m −3 ) often occurs near islands and bathymetric features such as on the Campbell Plateau, southeast of New Zealand. To investigate the processes responsible for localized increases in chl a commonly observed by satellites, we characterized phytoplankton biomass structure, production, and microzooplankton grazing on Campbell Plateau and surrounding waters in austral autumn (March 2017). Chl a on the plateau tended to be higher, more variable (0.52 ± 0.38 mg chl a m −3, mean ± standard deviation), and characterized by larger phytoplankton forms (22 ± 27%chl a > 20 μm) than surrounding waters (0.29 ± 0.12 mg chl a m −3, 5 ± 2%). The increased contribution of diatoms, together with higher photosystem II maximum photochemical efficiency (Fv/Fm = 0.45 ± 0.05) and lower effective absorption cross‐section (σPSII = 774 ± 90 Å RCII −1 ) on the plateau, suggests an alleviation of iron stress relative to surrounding waters (Fv/Fm = 0.37 ± 0.04, σPSII = 974 ± 89 Å RCII −1 ). Phytoplankton growth (μ0 = 0.42 ± 0.20 day −1 ) and production rates (6.1 ± 3.2 mg C m −3 day −1 ) were also higher compared to surrounding waters (0.27 ± 0.04 day −1, 3.5 ± 1.9 mg C m −3 day −1 ). While microzooplankton grazing (g = 0.28 ± 0.18 day −1 ) balanced phytoplankton growth off the plateau (g:μ0 = 1.13 ± 0.18), the imbalance observed on Campbell Plateau (g = 0.25 ± 0.25 day −1 ) allowed a substantial proportion of primary production to escape microzooplankton grazing control (g:μ0 = 0.48 ± 0.31). Overall, the degree of coupling tended to decrease with the depth of the mixed layer ( R 2 > 0.6, p < 0.001). We hypothesize that the entrainment of deeper water into the mixed layer regulates the onset and fate of the autumn bloom by altering nutrient supply and microzooplankton grazing pressure. Plain Language Summary: This study investigates controls on phytoplankton production processes in the Subantarctic region of the Southern Ocean. Low iron concentrations prevailing in this region limit phytoplankton growth and production rates, while phytoplankton biomass is further controlled by microzooplankton grazing. Despite these constraints, phytoplankton can thrive and accumulate, at least transiently, on nearby bathymetric features. We found that phytoplankton accumulation commonly observed in austral autumn on Campbell Plateau, southeast of New Zealand, presents floristic and physiological characteristics consistent with an alleviation of nutrient/iron stress relative to waters surrounding the plateau. While microzooplankton grazing balanced phytoplankton growth off the plateau, both processes tended to decouple on the plateau, which allowed a substantial proportion of phytoplankton production to escape microzooplankton control and phytoplankton biomass to accumulate. Overall, the net growth rate resulting from this (im)balance tended to increase with the depth of the upper mixed layer of the ocean, suggesting that changes in the stratification and mixing of the upper ocean can influence bottom‐up and top‐down processes controlling phytoplankton production. We hypothesize that by altering the rate of nutrient supply and the microzooplankton grazing pressure, the entrainment of the mixed layer regulates the onset and fate (recycling vs. export) of the autumn bloom. Key Points: Chlorophyll a concentration and the proportion of larger phytoplankton forms, and diatoms, tended to be higher on the Campbell Plateau Phytoplankton growth rate and primary productivity was enhanced on the plateau relative to surrounding waters Decoupling between phytoplankton growth and microzooplankton grazing rate on the plateau leading to positive net growth rates on the Campbell Plateau